Plot and structure : techniques and exercises for crafting a plot that grips readers from start to finish. - Bell, James Scott, ....- (Cincinnati (Ohio) : Writer's Digest, 2004)
The second book in the Write Great Fiction series, Plot and Structure offers clear and concise information on creating a believable and engaging plot that readers can't resist. Written by award-winning thriller and suspense author James Scott Bell, this handy instruction guide provides: Easy-to-understand techniques on every aspect of plotting and structure, from brainstorming story ideas to building scenes, and from using subplots to crafting knock-out endings; Engaging exercises, perfect for writers at any level and at any stage in their novel; Practical and encouraging guidance from one of the most respected writers publishing today; Full of diagrams, plot brainstormers, and examples from popular novels, mastering plot and structure has never been so simple.
Keywords: Scenario's.